Evaluating hearing results in stapedotomy: Comparison of fluoroplastic Causse loop piston and Matrix prosthesis - Mohammad Faramarzi; Pegah Pedramfard; Sareh Roosta; Tayebeh Kazemi; Hanie Aboughadare (Laryngoscope Investigative Otolaryngology, 2021)
Abstract Objective We carried out this research to assess and compare post‐stapedotomy hearing results of Matrix titanium prosthesis with a Teflon piston prosthesis, specifically the fluoroplastic (Teflon) Causse loop piston prosthesis in patients who suffered from otosclerosis. Methodology In this retrospective study, Causse loop piston prosthesis was used in 81 ears, and the Matrix prosthesis was applied in 44 ears. For pairwise matching with Matrix prosthesis, 44 out of 81 Causse loop piston‐treated ears were selected based on preoperative audiometric data. Then, postoperative audiometric results of these two groups were compared. The main outcomes were pure tone audiometric results and air‐bone gap (ABG) closure before and after the surgery. Incidence of postoperative sensorineural hearing loss was also evaluated and compared between the two groups. Results The results revealed no significant difference in improvement of speech reception threshold, mean air conduction, bone conduction gain, ABG closure, and incidence of postoperative sensorineural hearing loss at the frequencies of 0.5‐4 kHz between the two groups. However, performance of Matrix prosthesis was better in ABG closure at a frequency of 250 Hz. Conclusion Herein, similar postoperative improvement was achieved at the frequencies of 0.5‐4 kHz; nevertheless, Matrix provided better ABG closure at frequency of 250 Hz in short term. Level of Evidence 4